P-055 YI The Burden of Hospital Readmissions for Inflammatory Bowel Diseases. (February 2017) - Kochar, Bharati; Barnes, Edward; Martin, Christopher; Korzenik, Joshua; Long, Millie; Kappelman, Michael; Crockett, Seth
Abstract : Background: Hospital readmissions are a key metric associated with quality of health care. While IBD patients are frequently hospitalized for disease exacerbations or surgeries, there are a paucity of data on factors associated with hospital readmissions in IBD patients from nationally representative datasets. Methods: We used 2013 data from the National Readmissions Database (NRD), a nationally representative database from the Healthcare Cost and Utilization Project, in a retrospective cohort to describe IBD readmissions. With data from 21 states, the NRD can be used to create national estimates of readmission rates for all payers and the uninsured. International Classification of Diseases, ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes were used to identify adult patients with discharge diagnoses of ulcerative colitis (UC) or Crohn's disease (CD). Among patients >18 years of age with IBD, available demographic factors and details of the index hospitalization and readmissions were determined. Bivariate analyses were performed to describe factors associated with readmission. As there were no a priori hypotheses, statistical testing was not performed. Data were analyzed using SAS survey procedures. Results: There were 80, 203 CD and 48, 900 UC patients who were hospitalized in 2013. Of those who were hospitalized, 58% of CD patients and 54% of UC patients were female. The mean age was 51 years for CD patients and 56 years for UC patients. The median length of stay for the index hospitalization was 3.1 days for CD patients and 3.5 days for UC patients. In 2013, 20, 325 CD patients (25%) and 9694 (20%) UC patients were re-admitted within 90 days. Of the 80, 203 CD patients, 5549 (7%) had surgery during the index hospitalization; 1455 CD patients (26%) who had surgery during the index hospitalization were readmitted. Of the 48, 900 UC patients, 2691 (6%) had surgery during the index hospitalization, 632 UC patients (23%) who had surgery during the index hospitalization were readmitted. The median length of stay for a readmission was 3.6 days for CD patients and 4.0 days for UC patients. The 5 most frequent primary diagnoses for CD readmissions are as follows: Crohn's disease (32.8%), septicemia (3.6%), intestinal obstruction (3.3%), acute kidney failure (2.3%) and clostridium difficile intestinal infection (1.6%). The average cost for a CD readmission was $46, 203. The 5 most frequent primary diagnoses for a UC readmission are as follows: ulcerative colitis (34.8%), septicemia (4.2%), clostridium difficile intestinal infection (3.7%), acute kidney failure (1.7%) and pneumonia (1.2%). The average cost for a UC readmission was $54, 776. Conclusions: The rate of IBD readmissions are similar whether or not the index hospitalization involved surgery. After IBD itself, infections and acute kidney injury were some of the most common primary diagnosis codes for hospital readmission within 90 days. The cost of readmission is high. Understanding factors associated with hospital readmissions in the United States will help make progress toward improving quality of care for patients with IBD and reducing costs of readmission.